Rohingya refugee crisis in Bangladesh : its multi-dimensional implications - Muniruzzaman, ANM (2017)
There has been ethnic tension in Myanmar’s Rakhine State in recent years. The crisis has triggered a mass exodus into neighbouring Bangladesh generating security threats to the South Asian country.